1989
DOI: 10.1007/bf00155661
|View full text |Cite
|
Sign up to set email alerts
|

An application of Jones and James' perceived climate questionnaire in Australian higher educational institutions

Abstract: Attempts to explore the role of organisational climate in organisational effectiveness have been hampered by inadequacies in existing climate measures (e.g. Cameron, 1978aCameron, , 1978b. This paper describes the application of Jones & James (1979) perceived climate measures on a sample of senior level Australian academics. Six climate factors were identified: organisational conflict and ambiguity; two leadership components (facilitation and supportiveness, directiveness); work group cooperation in policy com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…see Cameron, 1986). Lysons and Ryder (1989, in press) found that the incorporation of the relevant PCQ scales assisted in the evaluation of the effectiveness of Australian universities and colleges. Stable factors of leadership and workgroup characteristics comparable to those discussed here were also identified in this large study involving senior-level university academics.…”
Section: Discussionmentioning
confidence: 99%
“…see Cameron, 1986). Lysons and Ryder (1989, in press) found that the incorporation of the relevant PCQ scales assisted in the evaluation of the effectiveness of Australian universities and colleges. Stable factors of leadership and workgroup characteristics comparable to those discussed here were also identified in this large study involving senior-level university academics.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the original set of questionnaire variables captured these dimensions without needing the support of the extended instrument employed in pursuit of added precision in the study. However, a major proportion of the common variance explained (39.9 of 85.4%) continued to involve "organisational health" which was noted as problematic for management to interpret and apply (Lysons & Ryder 1989). Indeed, organisational health emerged as the dominant effectiveness factor in all of the studies in the U.S., and Australian as well as the U.K. (Lysons & Hatherly 1992).…”
Section: Rationale Methods and Preliminary Results In The Ukmentioning
confidence: 99%
“…These studies collectively suggested the importance of managerial and organisational activities and processes in OE, and the competing values literature strongly supports this view (Quinn & Rohrbaugh 1983;Quinn & Cameron 1983;Whetten & Cameron 1984;Quinn 1988). The next logical step was, therefore, to define these issues by introducing aspects of psychological climate into the research program (Lysons & Ryder 1989). The eight factors that emerged from the combined analysis of OE and climate variables confirmed the relative strength and consistency of dimensions of climate versus the less well defined omnibus organisational health scale (Lysons 1990b: p. 291).…”
Section: Studies In Australian Higher Educationmentioning
confidence: 99%
“…Indeed, his questionnaire variables have proven to capture his dimensions more efficiently than the extended instrument employed in this study, although a major proportion of the common variance explained (39.9 of 85.4%) continues to involve 'organisational health' which is problematic for management to interpret and apply (Lysons and Ryder 1989).…”
Section: Discussion Conclusion and Summarymentioning
confidence: 99%